A case of lead poisoning due to snooker chalk. Issue 6 (1st December 2000) - Dargan, P I; Evans, P H; House, I M; Jones, A L
Abstract : A 3 year, 9 month old child with pica presented with a blood lead concentration of 1.74 μmol/l (360 μg/l). The source of poisoning was snooker chalk (lead content 7200 μg/g). She was treated with intravenous calcium disodium edetate chelation. Thirty months later her blood lead was 0.39 μmol/l (80 μg/l). This case illustrates the need to be vigilant for more unusual causes of lead poisoning in the home.